Taxonomic revision of the fruit fly genus Neoceratitis Hendel (Diptera: Tephritidae) - de Meyer, Marc; Freidberg, Amnon (Zootaxa, 2012)
Neoceratitis is revised to include six species. N. albiseta, from Madagascar, is described as new. Trirhithrum lycii var. min-imum Bezzi, 1924 is a junior synonym of Ceratitis lycii Coquillett, 1901, new synonym. All known and suspected hostassociations are within the family Solanaceae, with one species (N. cyanescens) infesting tomatoes and several species ofSolanum, whereas the other species with known hosts are associated with Lycium spp. Neoceratitis is probably similar toTrirhithrum Bezzi and particularly to the little known Paratrirhithrum Shiraki. Redescriptions (description in the case of the new species) and illustrations are provided for all the species, and a key to all the species is also provided.